Integrasi Kearifan Lokal dalam Pembelajaran IPAS untuk Menumbuhkan Sikap Peduli Lingkungan Siswa Sekolah Dasar - Mina Zuyyina Ramadhani; Ni'matul Aufa; Nida Adzkia; Zerdy Firnanda Ramadhan; Ahmad Suriansyah; Maimunah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the use of local wisdom in the teaching of Science and Social Studies (IPAS) as a strategy to cultivate environmental awareness among elementary school students. Local values—such as traditional conservation practices, community habits in maintaining nature, and culturally rooted environmental ethics—are integrated to help students understand ecological issues in a contextual and meaningful way. The approach is implemented through project-based learning, local environmental observation, and the exploration of cultural practices linked to IPAS topics. Findings indicate that incorporating local wisdom not only increases student engagement but also strengthens their ecological consciousness. Students become more active, responsible, and capable of applying environmentally friendly behavior in daily life. Therefore, integrating local wisdom into IPAS instruction serves as an effective method for developing students’ knowledge, attitudes, and skills in addressing contemporary environmental challenges.